2001
DOI: 10.1046/j.1365-263x.2001.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric antibiotic prescribing by general dental practitioners in England

Abstract: The results of this study show that some practitioners prescribe liquid-based antibiotics inappropriately for children. This may contribute to the problem of antimicrobial resistance. Clear guidelines on the choice of antibiotic, dose, frequency and duration along with educational initiatives for GDPs might reverse this trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…This lack of consensus for provid ing effective and immediate care to ensure a young child is relieved of pain is a major cause for concern and has been com mented upon by previous studies. 11,12 However, there was agree ment that doing nothing immediately and referring the child for extraction under general anaesthesia was not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of consensus for provid ing effective and immediate care to ensure a young child is relieved of pain is a major cause for concern and has been com mented upon by previous studies. 11,12 However, there was agree ment that doing nothing immediately and referring the child for extraction under general anaesthesia was not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies in the United Kingdom have consistently shown that there is widespread variation in the prescribing habits of GDPs, with many prescribing inappropriately, with inconsistent dose and frequency and often for prolonged periods. [4][5][6][7][8][9][10] This was also shown to be the case when patients sought advice and treatment from their general medical practitioners. 11 In a UK dental survey carried out by a major pharmaceutical company 12 looking at the factors infl uencing frequency and type of regularly prescribed antibiotic, 75% of dentists gave antibiotics at least once a week with over 15% of those dentists prescribing them on a daily basis.…”
Section: Introductionmentioning
confidence: 90%
“…[4][5][6][7][8][9][10][11] The defi nitive treatment of a dentoalveolar abscess is drainage and removal of the cause of the infection. 14,17,18,[29][30][31][32][33][34][35][36][37][38][39] In the majority of cases this is the only treatment required.…”
Section: Current Prescribing Practicesmentioning
confidence: 99%
“…The inappropriate use of antibiotics has contributed to the worldwide problem of antibiotic resistance [1,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Other problems include toxicity, allergic reactions and other side effects [4] . Superinfection with resistant bacteria may also result [5] .…”
Section: Introductionmentioning
confidence: 99%